Thermal emission from a single glass fiber. (October 2019) - Kallel, Houssem; Doumouro, Joris; Krachmalnicoff, Valentina; De Wilde, Yannick; Joulain, Karl
Highlights: The thermal radiation is measured using infrared spatial modulation spectroscopy. The optical properties of glass fibers are calculated using Mie Theory. The measured spectra are compared with the absorption efficiency spectra. The contribution of scattering of the thermal background by the fiber is discussed. Abstract: In this article, we study the thermal light emission from individual fibers of an industrial glass material, which are elementary building blocks of glass wool boards used for thermal insulation. Thermal emission spectra of single fibers of various diameters partially suspended on air are measured in the far field by means of infrared spatial modulation spectroscopy. These experimental spectra are compared with the theoretical absorption efficiency spectra of cylindrical shaped fibers calculated analytically in the framework of Mie theory taking as an input the measured permittivity of the industrial glass material. An excellent qualitative agreement is found between the measured thermal radiation spectra and the theoretical absorption efficiency spectra.